Pengaruh Medication Therapy Management (MTM) dalam Meningkatkan Pengetahuan yang Berimplikasi terhadap Kepatuhan Terapi Pasien Hipertensi di UPTD Puskesmas Sukamulya Kabupaten Majalengka - Permana, Agung; Yuliati, Farida; Asnar, Etty Sofia Mariati; Paramarta, Vip; Nugroho, Taufan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to analyze the influence of Medication Therapy Management (MTM) and knowledge levels on the therapeutic adherence of hypertensive patients at the UPTD Sukamulya Public Health Center. The research subjects consisted of 261 hypertensive patients who were selected as the sample. Data were analyzed using path analysis, correlation coefficient analysis, and coefficient of determination analysis. The results showed that, descriptively, Medication Therapy Management (MTM) was categorized as excellent, patients’ knowledge about hypertension was considered good, and their adherence to therapy was fairly good. However, some aspects remained low, especially regarding understanding of diastolic or systolic blood pressure and difficulties with medication use. The analysis results indicated that Medication Therapy Review (MTR) and Personal Medication Record (PMR) had a significant impact on the patients' knowledge about hypertension. On the other hand, Medication-related Action Plan (MAP), Intervention and/or Referral (I/R), and Documentation and Follow-up (Doc/F Up) did not significantly affect the patients' knowledge. Additionally, patients' knowledge about hypertension was found to significantly affect their therapeutic adherence. Overall, Medication Therapy Management (MTM) contributed significantly to improving therapeutic adherence among hypertensive patients by enhancing their knowledge about hypertension. The results emphasize that Medication Therapy Management (MTM) improves therapeutic adherence in hypertensive patients by enhancing their knowledge. Key components like Medication Therapy Review (MTR) and Personal Medication Record (PMR) should be prioritized, while other MTM aspects need refinement. Overall, improving patient education can boost adherence and reduce hypertension complications.